The Concept Of Reading According To The Qur'an Perspective - Al-Ghiffary, Ghalib Muhammad Syukri (International Journal of Cultural and Social Science, 2022)
This study analyzes the concept of reading in the perspective of the Qur'an. This theme was taken to illustrate that reading is very important and becomes a recommendation in Islam. This study focuses on Surah Al-Alaq verses 1-5 with the interpretations that will be used consisting of Tafsir Al-Misbah, Al-Azhar, Ath-Tabari, Ibn Kathir and Al-Maraghi. The objectives in this study include (1) To analyze the basic concept of reading according to the perspective of the Qur'an. (2) To analyze the concept of reading seen from the interpretations of Al-Misbah, Al Azhar, Ath-Tabari, Ibn Kathir and Al-maraghi. (3) To analyze the relevance of the concept of reading with the deepening of library science. This research is a research that uses literature study and content analysis methods. the first step is to conduct a literature study on the interpretations that discuss the concept of reading interest according to the perspective of the Qur'an. The results of this study indicate that the basic concept of reading according to the perspective of the Qur'an lies in the letter Al Alaq, especially verses one and three. different. The relevance of the concept of reading to the deepening of knowledge Library libraries can be interpreted that libraries provide information needs of users, because libraries provide collections that contain reference materials, provide teaching and knowledge as well as a place for learning sources of life. As explained in the verse of the Qur'an that those who are knowledgeable will get protection from Allah and a bounty for His servants.